Haematological and biochemical responses of juvenile malabar blood snapper (Lutjanus malabaricus Bloch & Schneider, 1801) exposed to different rearing temperatures and diets - Mazumder, Sabuj Kanti; Fivelstad, Sveinung; Mazlan Abd. Ghaffar,; Simon Kumar Das, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study is conducted to examine the impacts of different rearing temperature and diet variation on haematological and serum biochemical parameters on the juvenile Lutjanus malabaricus, a commercially important fish species in Malaysia. Fish (16-18 cm) were divided into eight treatments (4 temperatures × 2 diets) each with three replicates of five juveniles each. Fish were subjected to four different rearing temperatures (22, 26, 30 and 34°C) and fed with a commercial pellet and a natural shrimp diet. After 30 days of experimental period, blood samples were collected and transferred into two different tubes from each sample: One containing EDTA as an anticoagulant agent and the other without EDTA for serum collection. All the haematological and biochemical parameters in all the treatments were within the normal range. Changing temperature and diet led to a significant change (p<0.05) in the total length (TL), body weight (BW), red blood cell (RBC), haemoglobin (HB), haematocrit (HC), thrombocyte (TC) and white blood cell (WBC) but the change in mean corpuscular volume (MCV), mean cell haemoglobin (MCH) while mean cell haemoglobin concentration (MCHC) were not significant (p>0.05). The fish reared at 26°C and 30°C had significantly higher values than those reared at 22°C and 34°C (p<0.05). Total protein (TP), albumin (ALB), albumin/globin ration (A/G ratio), alkaline phosphatase (AP), aspartate aminotransferase (AST) and alanine transaminase (ALT) level were also significantly increased at 30°C and 26°C compared to that of 34°C and 22°C. Globulin (GLB) level showed the opposite trend. In all the cases the performances were higher in shrimp diet than pellet diet. It is suggested that these physiological parameters can be conveniently employed as health monitoring tools in fish culture practices.